1994
DOI: 10.1016/s0194-5998(94)70562-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computed tomography and surgical findings in deep neck infections

Abstract: Computed tomography is routinely used in the evaluation of patients suspected to have deep neck infections. This 10-year retrospective study compares preoperative computed tomography scan reports with intraoperative findings in 38 patients who underwent surgical exploration of the parapharyngeal or retropharyngeal space within 48 hours of their radiographic assessment. Overall, intraoperative findings confirmed computed tomography scan interpretation in 76.3% of the patients. The false-positive rate was 13.2%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 0 publications
5
55
0
6
Order By: Relevance
“…The presence of an enhancing rim around a nonenhancing central density differentiates cellulitis from an abscess; however, CT is not always able to differentiate between abscess and cellulitis and so helps us in deciding whether surgical drainage is indicated. In one review, the reported sensitivity of CT for the detection of lateral pharyngeal space and retropharyngeal space abscess was 88% [11] . After 1997, CT was routinely used to confi rm clinically suspected DNIs.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an enhancing rim around a nonenhancing central density differentiates cellulitis from an abscess; however, CT is not always able to differentiate between abscess and cellulitis and so helps us in deciding whether surgical drainage is indicated. In one review, the reported sensitivity of CT for the detection of lateral pharyngeal space and retropharyngeal space abscess was 88% [11] . After 1997, CT was routinely used to confi rm clinically suspected DNIs.…”
Section: Discussionmentioning
confidence: 99%
“…In differentiating deep neck abscesses from phlegmons, several large series have reported the false-positive rate to range from 8% to 25%. [7][8][9]21 Furthermore, Broughton 5 and Sichel et al 6 describe children who responded to treatment with intravenous antibiotics alone with significant CECT evidence of RAs defined by classic radiographic criteria of ring enhancement and large size. Many of the cases reported by Sichel and colleagues showed scalloped rim enhancement, thought by Kirse and Roberson 1 to be an important predictor of abscess formation.…”
Section: Commentmentioning
confidence: 99%
“…As infecções cervicais podem disseminar-se locoregionalmente através de diferentes vias como a hematogênica e a linfática, mas principalmente por extensão direta (contigüidade) dissecando por entre as fáscias, atingindo e envolvendo múltiplos espaços cervicais 7 .…”
Section: Apresentação Clínicaunclassified
“…Considerando as relações anatômicas entre os espaços e estruturas da face e a maior incidência de disseminação por extensão direta, é clássico o envolvimento de espaços específicos de acordo com o foco de origem da infecção 7 . As infecções odontogênicas acometem principalmente os espaços submandibular, submentoniano e sublingual e, posteriormente, o mastigatório e o parafaríngeo 8 .…”
Section: Apresentação Clínicaunclassified